Pengaruh Pendekatan Deep Learning terhadap Keterampilan Sosial Murid pada Pembelajaran IPAS Kelas III SDN Tegal Besar 02 Jember - Nuril Maulidya (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the limited social skills of students in IPAS learning, as indicated by the lack of cooperation, communication, and active participation among students. The purpose of this study was to determine the effect of the deep learning approach on the social skills of third-grade students at SDN Tegal Besar 02 Jember. The research method used was an experimental method with a pretest posttest control group design. The research subjects consisted of 55 students, including 28 students in the experimental class and 27 students in the control class. Data collection techniques used questionnaires and social skills observation sheets. The data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and n-gain tests with the assistance of SPSS version 25. The results showed that the average posttest score of the experimental class was higher than that of the control class, namely 70.54 > 54.63 based on observation data and 78.29 > 69.67 based on questionnaire data. The results of the t-test showed that the t count values of 4.036 for observation data and 2.992 for questionnaire data were greater than the t-table value of 2.006, so H₀ was rejected and Hₐ was accepted. This indicates that there was a significant effect of the implementation of the deep learning approach on students’ social skills. In addition, the results of the n-gain test showed that the improvement in social skills was in the moderate category, with scores of 0.4785 (observation) and 0.3085 (questionnaire). Based on these findings, it can be concluded that the deep learning approach has a significant and sufficiently effective effect on improving students’ social skills in IPAS learning.
Approved by Teddy
Keywords: Deep learning Approach; Social Skills; IPAS Learning; Elementary School Students